Advances in practical applications of survivable agents and multi-agent systems : the PAAMS Collection : 17th International Conference, PAAMS 2019, Ávila, Spain, June 26-28, 2019, Proceedings /: the PAAMS Collection : 17th International Conference, PAAMS 2019, Ávila, Spain, June 26-28, 2019, Proceedings. ([2019]) - Unknown
No abstract available